About the Cover - Robert Lucas (Case Western Reserve University, 2020)
About the CoverVirgin and Child with the Young Saint John the Baptist, c. 1490   Sandro Botticelli and Workshop (Italian, 1444/45-1510)   Italy, 15th century; Tempera and oil on wood; Framed: 115 x 12.5 cm (45 1/4 x 4 15/16 in.); Diameter: 68 cm (26 3/4 in.); Leonard C. Hanna, Jr. Fund 1970.160   Image Credit: Cleveland Museum of Art   SThe perfectly round form, called a tondo, became popular during the 1440s. Made for domestic settings instead of churches, the circular format challenged the artist to create a harmonious, balanced composition within this more difficult shape. The attribution has been a matter of debate. Botticelli often collaborated with students, including Filippino Lippi, who would himself become a significant painter. Few specialists have doubted that Botticelli executed the central passages: the delicate modeling of the faces, the graceful poses, the figures' profound interiority, and the diaphanous veil are the artist's hallmarks. However, someone else in Botticelli's studio probably painted Mary's blue garment, also the most heavily restored part of the painting.